Central African Republic : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses Central African Republic's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. Performance under the authorities' Emergency Post-Conflict Assistance (EPCA) program has been generally satisfactory through end-September 2006, taking into account the difficult external environment. Overall, the main objectives of the EPCA program for this year should be achieved, with a moderate increase in economic growth, an improved fiscal position, and some progress in structural policies. The authorities' program for 2007-09 aims to build a firm foundation for accelerating private sector-led growth and alleviating poverty.